2010
DOI: 10.1021/jm1012006
|View full text |Cite
|
Sign up to set email alerts
|

Novel Trisubstituted Benzimidazoles, Targeting Mtb FtsZ, as a New Class of Antitubercular Agents

Abstract: Libraries of novel trisubstituted benzimidazoles were created through rational drug design. A good number of these benzimidazoles exhibited promising MIC values in the range of 0.5-6 μg/mL (2-15 μM) for their antibacterial activity against Mtb H37Rv strain. Moreover, five of the lead compounds also exhibited excellent activity against clinical Mtb strains with different drugresistance profiles. All lead compounds do not show appreciable cytotoxicity (IC 50 >200 μM) against Vero cells, which inhibit Mtb FtsZ as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
145
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(150 citation statements)
references
References 28 publications
4
145
0
1
Order By: Relevance
“…Inhibition of FtsZ assembly has been shown to cause bacterial cell elongation and to inhibit bacterial proliferation [3,9,10]. In addition to its critical role in bacterial cytokinesis, FtsZ is a highly conserved protein in prokaryotes [11], thereby making it a promising antibacterial drug target [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of FtsZ assembly has been shown to cause bacterial cell elongation and to inhibit bacterial proliferation [3,9,10]. In addition to its critical role in bacterial cytokinesis, FtsZ is a highly conserved protein in prokaryotes [11], thereby making it a promising antibacterial drug target [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Through structural analysis of these compounds, Ojima and co-workers synthesized a number of new small organic molecules with the benzimidazole scaffold ( Figure 7) and evaluated their antimicrobial activity against M. tuberculosis H37Rv. Among these compounds, 44 and 45 ( Figure 7) were found to display MIC values lower that 1 μg mL −1 without any significant toxicity (IC 50 > 200 μM) against Vero cells [118]. Further investigation revealed that these compounds also showed similar potency against the drug-resistant M. tuberculosis strains.…”
Section: Benzimidazole Derivativesmentioning
confidence: 95%
“…Several trisubstituted benzimidazoles have previously been found to be effective against M. tuberculosis H37Rv strains [88]. Initial SAR studies indicated that a cyclohexyl group at the C2 position and diethylamino, dimethylamino or pyrrolidine group at the C6 position are crucial for antibacterial activity.…”
Section: Benzimidazolesmentioning
confidence: 99%